Case Report: A rare case of non-small cell lung cancer with STRN-ALK fusion in a patient in very poor condition treated with first-line ensartinib - Song, Guo-qiang; Li, Yi-zhong; Kong, Weiliang; Hu, Guo-qiang (Frontiers in Oncology, 2023)
Several cases of STRN-ALK fusion have been reported, and some anaplastic lymphoma kinase (ALK) inhibitors have been shown to be effective for treatment. Nevertheless, no cases of COVID-19 leading to heart failure and respiratory failure have been reported in people older than 70 years treated with ALK inhibitors. The present case report describes a 70-year-old patient with usual chronic obstructive pulmonary disease, diabetes, depression, and carotid plaque disease. Next-generation sequencing of tissue obtained by puncture biopsy revealed a STRN-ALK mutation accompanied by a TP53 mutation. The patient was treated with ensartinib and developed COVID-19 leading to heart failure and respiratory failure; nevertheless, he had a good clinical outcome and exhibited high treatment tolerability.